Abnormal Curtain Signs Identified With a Novel Lung Ultrasound Protocol in Six Dogs With Pneumothorax - Boysen, Søren; McMurray, Jantina; Gommeren, Kris (Frontiers in Veterinary Science, 2019)
Pneumothorax is typically ruled out sonographically by detecting a glide sign, lung pulse, and/or B lines, and ruled in by detecting the return of a glide sign and/or presence of a lung point. This case series describes novel lung ultrasound findings (abnormal curtain signs) in dogs with naturally-occurring pneumothorax. This case series also describes a novel lung ultrasound protocol that involves evaluating the curtain sign along the entire thoracoabdominal border and evaluating the ventral pleural space with the probe parallel to the ribs. Six dogs with pneumothorax (three traumatic pneumothorax and three spontaneous pneumothorax) had lung ultrasound performed. All dogs had normal synchronous curtain signs in the caudal mid-to-ventral region of the thorax and abnormal curtain signs in the caudal mid-to-dorsal thoracic regions. Five dogs had bilateral pneumothorax; four had a lung point and absence of a glide sign bilaterally, and one had a lung point identified unilaterally (a lung point was not visible on the opposite side and the glide sign was equivocal bilaterally). One dog had a unliteral pneumothorax, in which a lung point and absence of a glide sign were identified. With the probe parallel to the ribs in the ventral thorax, a small volume pleural effusion was also identified in two dogs. All dogs had mild to moderate quantities of pleural air removed via thoracentesis or chest tubes following lung ultrasound. Two distinct types of abnormal curtain sign were observed, referred to as the asynchronous curtain sign and the double curtain sign. The authors hypothesize that these abnormal curtain signs are caused by the presence of free air within and/or cranial to the costophrenic recess. To the authors’ knowledge, this is the first description of pneumothorax-induced abnormal curtain signs, and the first report of evaluating the curtain sign to diagnose pneumothorax in any species. Further research is required to determine the sensitivity and specificity of asynchronous and double curtain signs in diagnosing pneumothorax, and to investigate whether probe orientation parallel to the ribs in the ventral thorax will improve detection of pleural effusion.